Metadiscourse Analysis of Arabic Debate Argumentation at ISDC (International School Debating Championship) - Umam, Ahmad Zaimul; Al Farisi, Mohamad Zaka; Supriadi, Rinaldi (Master Program in Linguistics, Diponegoro University, 2024)
Arabic debate is an argumentative discourse with exceptional skills in conveying it; therefore, debaters are required not only to be proficient in the material but must also be able to use extraordinary rhetoric to satisfy the audience. This research analyzes the types and functions of Hyland metadiscourse markers used by debaters from the Indonesian team and the Singapore team in international inter-school debate events (ISDC) in Doha, Qatar. This research method uses descriptive qualitative research and a content analysis research design. Data collection techniques include listening and note-taking. At the data analysis stage, researchers carry out steps: collecting, reducing, presenting, and drawing conclusions. This research shows that all Indonesian and Singapore team debaters used all subcategories of Hyland's interactive and interactional metadiscourse marker categories. Metadiscourse is vital to conveying an idea or discourse so that the reader and audience can express and understand the concept well.